Dynamics and underlying causes of illegal bushmeat trade in Zimbabwe - Lindsey, P. A.; Romañach, S.S.; Matema, S.; Matema, C.; Mupamhadzi, I.; Muvengwi, J. (Oryx, 2011)
The prevalence and impacts of the illegal trade in bushmeat are under appreciated in Southern Africa, despite indications that it constitutes a serious conservation threat in parts of the region. Bushmeat trade has emerged as a severe threat to wildlife conservation and the viability of wildlife-based land uses in Zimbabwe during a period of political instability and severe economic decline. We conducted a study around Savé Valley Conservancy in the South-East Lowveld of Zimbabwe to investigate the dynamics and underlying causes of the bushmeat trade, with the objective of developing solutions. We found that bushmeat hunting is conducted mainly by unemployed young men to generate cash income, used mostly to purchase food. Bushmeat is mainly sold to people with cash incomes in adjacent communal lands and population centres and is popular by virtue of its affordability and availability. Key drivers of the bushmeat trade in the South-East Lowveld include: poverty, unemployment and food shortages, settlement of wildlife areas by impoverished communities that provided open access to wildlife resources, failure to provide stakes for communities in wildlife-based land uses, absence of affordable protein sources other than illegally sourced bushmeat, inadequate investment in anti-poaching in areas remaining under wildlife management, and weak penal systems that do not provide sufficient deterrents to illegal bushmeat hunters. Each of these underlying causes needs to be addressed for the bushmeat trade to be tackled effectively. However, in the absence of political and economic stability, controlling illegal bushmeat hunting will remain extremely difficult and the future of wildlife-based land uses will remain bleak.